Computed tomography and magnetic resonance imaging features of primary liver perivascular epithelioid cell tumor with renal angiomyolipoma: a case report and literature review - Ruoling Gao; Jiaying Liu; Qingdian Cong; Zhilan Huang; Guoping Zhu; Xuan Jin; Jibo Hu (Frontiers in Oncology)
Hepatic perivascular epithelioid cell tumor (PEComa) is an extremely rare mesenchymal tumor. The disease has few specific clinical symptoms and imaging manifestations, making its accurate diagnosis an intractable clinical challenge. This is a report of a female patient diagnosed with lesions and a mass in the left lobe of the liver. The computed tomography (CT) findings showed that the scan without a contrast agent had a slightly low density, and significant enhancement was seen in the arterial phase of the enhanced scan, with numerous tortuous arteries. The enhancement slightly decreased in the equilibrium phase and the delayed phase. The magnetic resonance imaging (MRI) findings were low signal for T1-weighted images (T1WI) and high signal for T2-weighted images (T2WI), and the enhancement pattern of the enhanced scan was similar to that of CT. Subsequently, the patient underwent surgical excision to remove the tumor. Based on the positive immunohistochemical staining for human melanoma black 45 (HMB45), smooth muscle actin (SMA), and melanin-A (Melan-A), a definitive diagnosis was made. Given that the pathological findings indicate low-grade malignancy, regular follow-up should be conducted. The patient presented with multiple fatty lesions in both kidneys, with the larger one located in the lower part of the left kidney, which was eventually confirmed as angiomyolipoma through surgical pathology. A literature review was carried out on the clinical features and imaging findings of the hepatic perivascular epithelioma, and cases with liver PEComa and kidney AML were described.